Relationship between preoperative lymphocyte to monocyte ratio and surgery outcome in type A aortic dissection - Ma, Ming; Zhu, Feng; Fan, Fudong; Pan, Jun; Cao, Hailong; Zhou, Qing; Wang, Dongjin (Frontiers in Surgery, 2023)
Background Lymphocyte-to-monocyte ratio (LMR) is associated with the mortality of cardiovascular diseases. However, the relationship between preoperative LMR and the prognosis of patients with Stanford type A aortic dissection (TAAD) undergoing surgical treatment remains to be determined. Methods We enrolled 879 patients with TAAD undergoing surgical treatment between January 2018 and December 2021. Patients were divided into two groups: the Deceased group and the Survived group. The baseline clinical and operative characteristics of the two groups were compared and analyzed. Results In univariate and multivariate logistic regression analysis, the association between LMR and in-hospital mortality was significant, and LMR (OR = 1.598, 95% CI 1.114–2.485, P = 0.022) remained significant after adjusting for confounders. Conclusion Lower LMR may be independently associated with higher in-hospital mortality in TAAD undergoing surgical treatment.